Lithium-containing electrode comprising ceramic particles and method for making the same

By applying ceramic particles on the surface or inside of the lithium metal electrode of the lithium ion battery pack to form a ceramic layer or embedded electrode surface, the problem of reduced efficiency caused by thickening of the SEI layer and early battery failure is solved, and higher Coulomb efficiency and Better battery performance.

CN114914399BActive Publication Date: 2025-02-18GM GLOBAL TECHNOLOGY OPERATIONS LLC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202111516582.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-02-10
Filing Date
2021-12-13
Publication Date
2025-02-18
Estimated Expiration
2041-12-13

AI Technical Summary

Technical Problem

During the repeated cycle of existing lithium-ion battery packs, the solid electrolyte interface phase (SEI) layer becomes thicker, resulting in a decrease in Coulomb efficiency and a premature battery failure.

Method used

Apply ceramic particles, such as lithium lanthanum zirconium oxide (LLZO), alumina and zirconium oxide particles, to form a ceramic layer or embedded in the electrode surface to improve the ion transport and mechanical robustness of the SEI layer.

Benefits of technology

By improving the quality of the SEI layer, smooth lithium deposition is promoted, and the Coulomb efficiency, rate performance and fast charging capability of the lithium-ion battery pack are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114914399B_ABST
    Figure CN114914399B_ABST
Patent Text Reader

Abstract

The present invention discloses a lithium-containing electrode comprising ceramic particles and a method for making the same. A lithium metal electrode comprising ceramic particles, an electrochemical cell comprising the lithium metal electrode, and a method for making the lithium metal electrode are provided herein. The lithium metal electrode comprises ceramic particles in the form of: a ceramic layer adjacent to a first surface of the lithium metal electrode, embedded in the first surface, or a combination thereof. The ceramic particles comprise lithium lanthanum zirconium oxide (LLZO) particles, aluminum oxide particles, or a combination thereof.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to lithium metal electrodes comprising ceramic particles (eg, in the form of a ceramic layer), electrochemical cells including the lithium metal electrodes, and methods of making lithium metal electrodes comprising ceramic particles. Background Art

[0002] This section provides background information related to the present disclosure which is not necessarily prior art.

[0003] High energy density electrochemical cells, such as lithium-ion batteries, can be used in a variety of consumer products and vehicles, such as hybrid electric vehicles (HEVs) and electric vehicles (EVs). A typical lithium-ion battery includes a first electrode (e.g., a cathode), a second electrode (e.g., an anode) of opposite polarity, an electrolyte material, and a separator. Conventional lithium-ion batteries operate by reversibly transferring lithium ions between a negative electrode and a positive electrode. The separator and electrolyte are disposed between the negative electrode and the positive electrode. The electrolyte is suitable for conducting lithium ions and can be in solid, semi-solid, or liquid form. Lithium ions move from the cathode (positive electrode) to the anode (negative electrode) during the battery charging process, and move in the opposite direction when the battery is discharged. For convenience, the negative electrode will be used synonymously with the anode, although as recognized by those skilled in the art, at certain stages of the lithium-ion cycle, the anode function may be associated with the positive electrode rather than the negative electrode (e.g., the negative electrode may be the anode during discharge and the cathode during charging).

[0004] In various aspects, the electrode comprises an electroactive material. The negative electrode generally comprises an electroactive material capable of acting as a lithium host material for use as a negative terminal of a lithium ion battery. Conventional negative electrodes comprise an electroactive lithium host material and optionally another conductive material such as carbon black particles, and one or more polymer binder materials to hold the lithium host material and the conductive particles together.

[0005] The lithium-ion battery pack can reversibly supply power to an associated load device as needed. More specifically, power can be provided to the load device by the lithium-ion battery pack until the lithium content of the negative electrode is effectively depleted. The battery pack can then be recharged by passing a suitable direct current in the opposite direction between the electrodes.

[0006] During discharge, the negative electrode may contain a relatively high concentration of intercalated lithium, which is oxidized into lithium ions and electrons. Lithium ions may travel from the negative electrode (anode) to the positive electrode (cathode), for example, through an ion-conducting electrolyte solution contained within the pores of an intercalated porous separator. At the same time, electrons are transferred from the negative electrode to the positive electrode via an external circuit. The lithium ions may be assimilated into the material of the positive electrode by an electrochemical reduction reaction. The battery pack may be recharged after its available capacity is partially or completely discharged by an external power source, which reverses the electrochemical reactions that occur during discharge.

[0007] During the recharge process, the intercalated lithium in the positive electrode is oxidized into lithium ions and electrons. The lithium ions travel from the positive electrode to the negative electrode via the electrolyte through the porous separator, and the electrons are transferred to the negative electrode through an external circuit. The lithium cations are reduced to elemental lithium at the negative electrode and stored in the material of the negative electrode for reuse.

[0008] During cycling, a passivation layer, also called a solid electrolyte interface (SEI) layer, is formed on the surface of the lithium-containing negative electrode by the decomposition products of the electrolyte. The SEI layer can play a role in preventing further decomposition of the electrolyte to maintain cycling capability, which requires the SEI layer to be well attached to the negative electrode, have good ion transport of lithium ions, be mechanically robust, and have good electronic insulating properties. However, during repeated cycling, the SEI layer on the lithium-containing negative electrode may become thicker and lead to lower Coulombic efficiency and premature battery failure, for example due to faster electrolyte consumption.

[0009] It is desirable to develop materials for lithium-ion batteries for use in high energy and high power lithium-ion batteries that overcome the shortcomings that currently prevent their widespread commercial application. Therefore, it is desirable to develop materials for lithium-ion batteries, especially materials for lithium-containing negative electrodes, which improve the quality of the SEI layer, such as improving the ion transport and mechanical robustness of the SEI layer, and promoting smooth lithium deposition, and thereby improving coulombic efficiency, rate performance and fast charging capability. Summary of the invention

[0010] This section provides a general summary of the disclosure, and is not a comprehensive disclosure of its full scope or all of its features.

[0011] In certain aspects, the present disclosure provides a lithium metal electrode. The lithium metal electrode includes a first surface and ceramic particles. The ceramic particles may include lithium lanthanum zirconium oxide (LLZO) particles, aluminum oxide particles, zirconium oxide particles, or a combination thereof. The ceramic particles may be present in the form of a ceramic layer adjacent to at least a portion of the first surface, embedded within the first surface, or a combination thereof. The ceramic layer may have a thickness of about 1 μm to about 100 μm.

[0012] The LLZO particles may be selected from:

[0013] Li (7-3y) Al y La3Zr2O 12 , where 0 ≤ y ≤ 2 / 3; Li 7+x-3y-z La 3-x (M) x (N) y Zr 2-z (Q)z O 12 , wherein M is Ca, Ba, Mg or Sr; N is Al or (3 / 4)Ge; Q is Ta or Nb; 0 ≤ x ≤ 1; 0 ≤ y ≤ 2 / 3; 0 ≤ z ≤ 2; and 5 ≤ (7 + x - 3y - z) ≤ 7; or a combination. In addition, the LLZO particles, the aluminum oxide particles, and the zirconium oxide particles may each have an average particle size of about 100 nm to about 20 μm.

[0014] The LLZO particles can be 2 Up to about 50 g / cm 2 In addition, the aluminum oxide particles may be present in an amount of 0.4 g / cm 2 Up to about 40 g / cm 2 In addition, the zirconium oxide particles may be present in an amount of about 0.5 g / cm 2 Up to about 50 g / cm 2 The amount exists.

[0015] A binder may be present with the ceramic particles, and the binder may coat at least a portion of the ceramic particles.

[0016] The ceramic particles may be present in a form embedded in the first surface.

[0017] The lithium metal electrode may include metallic lithium.

[0018] In yet other aspects, the present disclosure provides an electrochemical cell. The electrochemical cell includes a lithium metal negative electrode including a first surface and ceramic particles. The ceramic particles may include lithium lanthanum zirconium oxide (LLZO) particles, aluminum oxide particles, zirconium oxide particles, or a combination thereof. The ceramic particles may be present in the form of a ceramic layer adjacent to at least a portion of the first surface, embedded in the first surface, or a combination thereof. The ceramic layer may have a thickness of about 1 µm to about 100 µm. The electrochemical cell may also include a positive electrode including a second electroactive material. The positive electrode may be spaced apart from the lithium metal negative electrode. The electrochemical cell may also include a porous diaphragm disposed between the confronting surfaces of the lithium metal negative electrode and the positive electrode, and a liquid electrolyte that permeates one or more of the lithium metal negative electrode, the positive electrode, and the porous diaphragm.

[0019] The LLZO particles may be selected from:

[0020] Li (7-3y) Al y La3Zr2O 12, where 0 ≤ y ≤ 2 / 3; Li 7+x-3y-z La 3-x (M) x (N) y Zr 2-z (Q) z O 12 , where M is Ca, Ba, Mg or Sr; N is Al or (3 / 4)Ge; Q is Ta or Nb; 0 ≤ x ≤ 1; 0 ≤ y ≤ 2 / 3; 0 ≤ z ≤ 2; and 5 ≤ (7 + x - 3y - z) ≤ 7; or a combination. In addition, the LLZO particles, the alumina particles and the zirconia particles may each have an average particle size of about 100 nm to about 20 µm.

[0021] The LLZO particles may be present in an amount of 0.5 g / cm 2 to about 50 g / cm 2 . In addition, the alumina particles may be present in an amount of 0.4 g / cm 2 to about 40 g / cm 2 . In addition, the zirconia particles may be present in an amount of about 0.5 g / cm 2 to about 50 g / cm 2 .

[0022] A binder may be present with the ceramic particles, and the binder may coat at least a portion of the ceramic particles.

[0023] The ceramic particles may be present in a form embedded in the first surface.

[0024] The lithium metal electrode may comprise metallic lithium. The second electroactive material may include Li (1+x) Mn2O4, where 0.1 ≤ x ≤ 1; LiMn (2-x) Ni x O4, where 0 ≤ x ≤ 0.5; LiCoO2; Li(Ni x Mn y Co z )O2, where 0 ≤x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, and x + y + z = 1; LiNi (1-x-y) Co x M y O2, where 0 < x < 0.2, y < 0.2, and M is Al, Mg or Ti; LiFePO4, LiMn 2-x Fe xPO4, wherein 0 < x < 0.3; LiNiCoAlO2; LiMPO4, wherein M is at least one of Fe, Ni, Co and Mn; Li(Ni x Mn y Co z Al p )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ P ≤ 1, x + y + z + p = 1 (NCMA); LiNiMnCoO2; Li2Fe x M 1-x PO4, where M is Mn and / or Ni, 0 ≤ x ≤ 1; LiMn2O4; LiFeSiO4; LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622), LiMnO2 (LMO), activated carbon, sulfur and their combinations.

[0025] In yet other aspects, the present disclosure provides a method for preparing a lithium metal electrode. The method includes applying ceramic particles to a first surface of a lithium metal electrode to form a ceramic layer comprising ceramic particles. The ceramic layer may be adjacent to at least a portion of the first surface and may have a thickness of about 1 μm to about 100 μm. Applying the ceramic particles may include dry casting or slurry casting. The ceramic particles may include lithium lanthanum zirconium oxide (LLZO) particles, aluminum oxide particles, zirconium oxide particles, or a combination thereof.

[0026] The LLZO particles may be selected from:

[0027] Li (7-3y) Al y La3Zr2O 12 , where 0 ≤ y ≤ 2 / 3; Li 7+x-3y-z La 3-x (M) x (N) y Zr 2-z (Q) z O 12 , wherein M is Ca, Ba, Mg or Sr; N is Al or (3 / 4)Ge; Q is Ta or Nb; 0 ≤ x ≤ 1; 0 ≤ y ≤ 2 / 3; 0 ≤ z ≤ 2; and 5 ≤ (7 + x - 3y - z) ≤ 7; or a combination. In addition, the LLZO particles, the aluminum oxide particles, and the zirconium oxide particles may each have an average particle size of about 100 nm to about 20 μm.

[0028] The LLZO particles can be2 Up to about 50 g / cm 2 In addition, the aluminum oxide particles may be present in an amount of 0.4 g / cm 2 Up to about 40 g / cm 2 In addition, the zirconium oxide particles may be present in an amount of about 0.5 g / cm 2 Up to about 50 g / cm 2 The amount exists.

[0029] A binder may be applied with the ceramic particles, and the binder may coat at least a portion of the ceramic particles.

[0030] The method may further include pressing the ceramic layer to embed the ceramic particles within the first surface.

[0031] Applying the ceramic particles may be slurry casting, and the slurry may be applied to the first surface. The slurry may include a solvent and ceramic particles.

[0032] The method may further include drying the slurry applied to the first surface of the lithium metal negative electrode to remove the solvent.

[0033] The present invention discloses the following embodiments:

[0034] Scheme 1. Lithium metal electrode, comprising:

[0035] a first surface; and

[0036] Ceramic particles comprising:

[0037] (i) lithium lanthanum zirconium oxide (LLZO) particles;

[0038] (ii) aluminum oxide particles;

[0039] (iii) zirconium oxide particles; or

[0040] (iv) any combination thereof;

[0041] The ceramic particles are present in the following forms:

[0042] (i) a ceramic layer adjacent to at least a portion of the first surface, wherein the ceramic layer has a thickness of about 1 µm to about 100 µm;

[0043] (ii) embedded in said first surface; or

[0044] (iii) combinations thereof.

[0045] Scheme 2. The lithium metal electrode according to Scheme 1, wherein one or more of the following is satisfied:

[0046] (i) The LLZO particles are selected from:

[0047] Li (7-3y) Al y La3Zr2O 12 , where 0 ≤ y ≤ 2 / 3; Li 7+x-3y-z La 3-x (M) x (N) y Zr 2-z (Q) z O 12 , wherein M is Ca, Ba, Mg or Sr; N is Al or (3 / 4)Ge; Q is Ta or Nb; 0 ≤ x ≤ 1; 0 ≤ y ≤ 2 / 3; 0 ≤ z ≤2; and 5 ≤ (7 + x - 3y - z) ≤ 7; or a combination thereof; and

[0048] (ii) the LLZO particles, the aluminum oxide particles, and the zirconium oxide particles each have an average particle size of about 100 nm to about 20 µm.

[0049] Scheme 3. The lithium metal electrode according to Scheme 1, wherein one or more of the following is satisfied:

[0050] (i) The LLZO particles are 0.5 g / cm 2 Up to about 50 g / cm 2 The amount exists;

[0051] (ii) The alumina particles are 0.4 g / cm 2 Up to about 40 g / cm 2 exists in an amount; and

[0052] (iii) The zirconium oxide particles are approximately 0.5 g / cm 2 Up to about 50 g / cm 2 The amount exists.

[0053] Embodiment 4. The lithium metal electrode according to Embodiment 1, wherein a binder is present together with the ceramic particles, and the binder coats at least a portion of the ceramic particles.

[0054] Option 5. The lithium metal electrode according to Option 1, wherein the ceramic particles are present in a form embedded in the first surface.

[0055] Option 6. A lithium metal electrode according to Option 1, wherein the lithium metal electrode comprises metallic lithium.

[0056] Scheme 7. An electrochemical cell comprising:

[0057] Lithium metal negative electrode

[0058] a first surface; and

[0059] Ceramic particles comprising:

[0060] (i) lithium lanthanum zirconium oxide (LLZO) particles;

[0061] (ii) aluminum oxide particles;

[0062] (iii) zirconium oxide particles; or

[0063] (iv) any combination thereof;

[0064] The ceramic particles are present in the following forms:

[0065] (i) a ceramic layer adjacent to at least a portion of the first surface, wherein the ceramic layer has a thickness of about 1 µm to about 100 µm;

[0066] (ii) embedded in said first surface; or

[0067] (iii) any combination thereof;

[0068] a positive electrode comprising a second electroactive material, wherein the positive electrode is spaced apart from the lithium metal negative electrode;

[0069] a porous separator disposed between facing surfaces of the lithium metal negative electrode and the positive electrode; and

[0070] A liquid electrolyte permeates one or more of the lithium metal negative electrode, the positive electrode, and the porous separator.

[0071] Scheme 8. The electrochemical cell according to Scheme 7, wherein one or more of the following is satisfied:

[0072] (i) The LLZO particles are selected from:

[0073] Li (7-3y) Al y La3Zr2O 12 , where 0 ≤ y ≤ 2 / 3; Li 7+x-3y-z La 3-x (M) x (N) y Zr 2-z (Q) z O 12, wherein M is Ca, Ba, Mg or Sr; N is Al or (3 / 4)Ge; Q is Ta or Nb; 0 ≤ x ≤ 1; 0 ≤ y ≤ 2 / 3; 0 ≤ z ≤2; and 5 ≤ (7 + x - 3y - z) ≤ 7; or a combination thereof; and

[0074] (ii) the LLZO particles, the aluminum oxide particles, and the zirconium oxide particles each have an average particle size of about 100 nm to about 20 µm.

[0075] Scheme 9. The electrochemical cell according to Scheme 7, wherein one or more of the following is satisfied:

[0076] (i) The LLZO particles are 0.5 g / cm 2 Up to about 50 g / cm 2 The amount exists;

[0077] (ii) The alumina particles are 0.4 g / cm 2 Up to about 40 g / cm 2 exists in an amount; and

[0078] (iii) The zirconium oxide particles are approximately 0.5 g / cm 2 Up to about 50 g / cm 2 The amount exists.

[0079] Embodiment 10. The electrochemical cell of Embodiment 7, wherein a binder is present with the ceramic particles, and the binder coats at least a portion of the ceramic particles.

[0080] Embodiment 11. The electrochemical cell according to Embodiment 7, wherein the ceramic particles are present in a form embedded in the first surface.

[0081] Embodiment 12. The electrochemical cell according to Embodiment 7, wherein the lithium metal electrode comprises metallic lithium, and wherein the second electroactive material is selected from: Li (1+x) Mn2O4, where 0.1 ≤ x ≤ 1; LiMn (2-x) Ni x O4, where 0 ≤ x ≤ 0.5; LiCoO2; Li(Ni x Mn y Co z )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, and x + y +z = 1; LiNi (1-x-y) Co x M yO2, where 0 < x < 0.2, y < 0.2, and M is Al, Mg, or Ti; LiFePO4, LiMn 2-x Fe x PO4, where 0 < x < 0.3; LiNiCoAlO2; LiMPO4, where M is at least one of Fe, Ni, Co, and Mn; Li(Ni x Mn y Co z Al p )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ P ≤ 1, x + y + z + p = 1 (NCMA); LiNiMnCoO2; Li2Fe x M 1-x PO4, where M is Mn and / or Ni, 0 ≤ x ≤ 1; LiMn2O4; LiFeSiO4; LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622), LiMnO2 (LMO), activated carbon, sulfur, and combinations thereof.

[0082] Solution 13. A method for preparing a lithium metal electrode, the method comprising:

[0083] Applying ceramic particles to a first surface of the lithium metal electrode to form a ceramic layer comprising the ceramic particles, wherein the ceramic layer is adjacent to at least a portion of the first surface and has a thickness of from about 1 µm to about 100 µm;

[0084] wherein applying the ceramic particles comprises dry casting or slurry casting; and

[0085] wherein the ceramic particles comprise:

[0086] (i) Lithium lanthanum zirconium oxide (LLZO);

[0087] (ii) Alumina particles;

[0088] (iii) Zirconia particles; or

[0089] (iv) Combinations thereof.

[0090] Solution 14. The method according to Solution 13, wherein one or more of the following are satisfied:

[0091] (i) The LLZO particles are selected from:

[0092] Li (7-3y) Al y La3Zr2O 12, where 0 ≤ y ≤ 2 / 3; Li 7+x-3y-z La 3-x (M) x (N) y Zr 2-z (Q) z O 12 , wherein M is Ca, Ba, Mg or Sr; N is Al or (3 / 4)Ge; Q is Ta or Nb; 0 ≤ x ≤ 1; 0 ≤ y ≤ 2 / 3; 0 ≤ z ≤2; and 5 ≤ (7 + x - 3y - z) ≤ 7; or a combination thereof; and

[0093] (ii) the LLZO particles, the aluminum oxide particles, and the zirconium oxide particles each have an average particle size of about 100 nm to about 20 µm.

[0094] Scheme 15. The method according to Scheme 13, wherein one or more of the following is satisfied:

[0095] (i) The LLZO particles are 0.5 g / cm 2 Up to about 50 g / cm 2 The amount exists;

[0096] (ii) The alumina particles are 0.4 g / cm 2 Up to about 40 g / cm 2 exists in an amount; and

[0097] (iii) The zirconium oxide particles are approximately 0.5 g / cm 2 Up to about 50 g / cm 2 The amount exists.

[0098] Embodiment 16. The method according to embodiment 13, wherein a binder is applied together with the ceramic particles, and the binder coats at least a portion of the ceramic particles.

[0099] Option 17. The method according to Option 13 further includes pressing the ceramic layer so that the ceramic particles are embedded in the first surface.

[0100] Option 18. The method according to Option 13, wherein applying the ceramic particles is slurry casting, which includes applying a slurry onto the first surface, wherein the slurry comprises a solvent and the ceramic particles.

[0101] Embodiment 19. The method according to Embodiment 18 further comprises drying the slurry applied to the first surface of the lithium metal negative electrode to remove the solvent.

[0102] Further areas of applicability will become apparent from the description provided herein.The description and specific examples in this summary are intended for purposes of illustration only and are not intended to limit the scope of the present disclosure. BRIEF DESCRIPTION OF THE DRAWINGS

[0103] The drawings described herein are for illustrative purposes only of selected embodiments and not all possible implementations, and are not intended to limit the scope of the present disclosure.

[0104] Figure 1 is a schematic diagram of an exemplary electrochemical battery cell;

[0105] Figures 2A-2D is a schematic diagram of an exemplary lithium metal electrode including ceramic particles;

[0106] Figure 3 is a schematic diagram of an exemplary battery pack;

[0107] Figures 4A-4D is an exemplary schematic diagram illustrating a method of manufacturing a lithium metal electrode including ceramic particles;

[0108] Figures 5A-5C . Figure 5A are photographic images of the control anode, anode 2, and anode 6 formed according to Example 1. Figure 5B and 5C is a scanning electron microscope (SEM) image of the anode 2 formed according to Example 1;

[0109] Figure 6A-6B . Fig. 6A is a graph depicting capacity (mAh) versus cycle number for Batteries 2, 3, 5, and 6 formed according to Example 2 and Control Battery A following regular cycling conditions. Figure 6B is a graph depicting Coulombic efficiency versus cycle number for Cells 2, 3, 5, and 6 formed according to Example 2 and Control Cell A following basic cycling conditions;

[0110] Figure 7A-7B . Fig. 7A is a graph depicting capacity (mAh) versus cycle number for Batteries 1 and 4 formed according to Example 2 and Control Battery A following rapid charge cycling conditions. Figure 7B is a graph depicting Coulombic efficiency versus cycle number for Cells 1 and 4 formed according to Example 2 and Control Cell A following fast charge cycling conditions;

[0111] Figures 8A-8C . Fig. 8A are photographic images of the anodes from Control Cell A, Cell 2, Cell 3, and Cell 6 after cycling. Figure 8B and 8CSEM images of the anode surface of control cell A and cell 6 after basic cycling conditions, respectively;

[0112] Figures 9A-9B . Fig.9A is a graph depicting capacity (mAh) versus cycle number for Batteries 7 and 8 formed according to Example 3 and Control Battery A following regular cycling conditions. Fig. 9B is a graph depicting the Coulombic efficiency versus cycle number for Cells 7 and 8 formed according to Example 3 and Control Cell A following regular cycling conditions; and

[0113] Figures 10A-10B . Fig. 10A is a graph depicting capacity (mAh) versus cycle number for Batteries 9 and 10 formed according to Example 3 and Control Battery A following rapid charge cycling conditions. Fig. 10B is a graph depicting Coulombic efficiency versus cycle number for Cells 9 and 10 formed according to Example 3 and Control Cell A following rapid charge cycling conditions.

[0114] Corresponding reference numerals indicate corresponding parts throughout the several views of the drawings. DETAILED DESCRIPTION

[0115] Example embodiments will now be described more fully with reference to the accompanying drawings.

[0116] Exemplary embodiments are provided to make the disclosure thorough and fully convey its scope to those skilled in the art. Many specific details, such as examples of specific compositions, components, devices and methods, are set forth to provide a full understanding of the embodiments of the present disclosure. It will be apparent to those skilled in the art that specific details need not be used, and that the exemplary embodiments may be embodied in many different forms, none of which should be considered to limit the scope of the present disclosure. In some exemplary embodiments, well-known methods, well-known device structures and well-known technologies are not described in detail.

[0117] The terms used herein are intended to be limited only for the purpose of describing specific exemplary embodiments. Unless the context clearly indicates otherwise, the singular forms "one", "one / a kind of" and "the" used herein may be intended to also include plural forms. The terms "containing", "including", "comprising" and "having" are inclusive, and therefore specify the presence of the features, elements, compositions, steps, integers, operations and / or components, but do not exclude the presence or addition of one or more other features, integers, steps, operations, elements, components and / or their groups. Although the open term "comprising" is to be understood as a non-limiting term for describing and claiming the various embodiments described herein, in some aspects, the term may be alternatively understood as a more restrictive and limited term, such as "consisting of..." or "consisting essentially of..." Therefore, for any given embodiment of narrating compositions, materials, components, elements, features, integers, operations and / or method steps, the present disclosure also specifically includes embodiments consisting of or essentially consisting of such compositions, materials, components, elements, features, integers, operations and / or method steps. In the case of “consisting of,” alternative embodiments exclude any additional compositions, materials, components, elements, features, integers, operations and / or method steps, while in the case of “consisting essentially of,” any additional compositions, materials, components, elements, features, integers, operations and / or method steps that substantially affect the basic and novel characteristics are excluded from such embodiments, but any compositions, materials, components, elements, features, integers, operations and / or method steps that do not substantially affect the basic and novel characteristics may be included in such embodiments.

[0118] Any method steps, processes, and operations described herein should not be construed as necessarily requiring their performance in the particular order discussed or illustrated, unless expressly identified as an order of performance. It should also be understood that additional or alternative steps may be employed unless otherwise specified.

[0119] When a component, element, or layer is referred to as being "on another element or layer," "engaged with another element or layer," "connected to another element or layer," "attached to another element or layer," or "coupled to another element or layer," it may be directly on, directly engaged with, directly connected to, directly attached to, or directly coupled to the other component, element, or layer, or there may be intermediate elements or layers. In contrast, when an element is referred to as being "directly on another element or layer," "directly engaged with another element or layer," "directly connected to another element or layer," "directly attached to," or "directly coupled to another element or layer," there may be no intermediate elements or layers. Other words used to describe the relationship between elements should be interpreted in a similar manner (e.g., "between" vs. "directly between," "adjacent" vs. "directly adjacent," etc.). The term "and / or" as used herein includes any and all combinations of one or more associated enumerated items.

[0120] Although the term first, second, third etc. can be used to describe various steps, elements, components, regions, layers and / or sections in this article, these steps, elements, components, regions, layers and / or sections should not be limited by these terms unless otherwise specified. These terms can only be used to distinguish a step, element, component, region, layer or section from another step, element, component, region, layer or section. Unless clearly indicated by the context, terms such as "first", "second" and other numerical terms do not imply order or sequence when used in this article. Therefore, the first step, element, component, region, layer or section discussed below can be referred to as the second step, element, component, region, layer or section, without departing from the teaching of exemplary embodiments.

[0121] For ease of description, spatially or temporally related terms may be used herein, such as "before", "after", "inside", "outside", "below", "below", "lower", "above", "upper", etc. to describe the relationship between an element or feature and another one or more elements or features as shown in the accompanying drawings. Spatially or temporally related terms may be intended to include different orientations of the device or system in use or operation in addition to the orientation depicted in the accompanying drawings. For example, if the device in the figure is turned over, the elements described as being "below" or "below" other elements or features will then be oriented to be "above" other elements or features. Therefore, the exemplary term "below" can include orientations above and below. The device can be oriented in other ways (rotated 90 degrees or in other orientations), and the spatially related descriptors used in this article are interpreted accordingly.

[0122] It should be understood that for any description of a method, composition, apparatus, or system that “comprises” certain steps, ingredients, or features, it is also contemplated that, in certain alternative variations, such a method, composition, apparatus, or system may also “consist essentially of the enumerated steps, ingredients, or features,” thereby excluding any other steps, ingredients, or features that materially alter the basic and novel characteristics of the invention.

[0123] Throughout this disclosure, numerical values ​​represent approximate measurements or range limits to include minor deviations from a given value and embodiments with approximately the values ​​mentioned and embodiments with the exact values ​​mentioned. Except in the working examples provided at the end of the specific embodiments, all numerical values ​​of parameters (such as amounts or conditions) in this specification (including the appended claims) are to be understood as being modified by the term "approximately" in all cases, regardless of whether "approximately" actually appears before the numerical value. "Approximately" means that the numerical value allows a certain slight imprecision (close to the accuracy of the value to a certain extent; approximately or reasonably close to the value; almost). If the imprecision provided by "approximately" is not otherwise understood in this art with this common meaning, the "approximately" used herein at least represents the changes that may be caused by the common methods of measuring and using such parameters. For example, "approximately" can include less than or equal to 5%, optionally less than or equal to 4%, optionally less than or equal to 3%, optionally less than or equal to 2%, optionally less than or equal to 1%, optionally less than or equal to 0.5% and optionally less than or equal to 0.1% in some aspects.

[0124] Furthermore, the disclosure of ranges includes all values ​​within the entire range and disclosure of further subdivided ranges, including the endpoints and sub-ranges given for the stated range.

[0125] Example embodiments will now be described more fully with reference to the accompanying drawings.

[0126] I. Electrochemical Cells

[0127] A lithium-containing electrochemical cell typically includes a negative electrode, a positive electrode, an electrolyte for conducting lithium ions between the negative electrode and the positive electrode, and a porous separator between the negative electrode and the positive electrode that physically separates and electrically insulates the electrodes from each other while allowing free ion flow. When assembled in an electrochemical cell, such as a lithium-ion battery pack, the porous separator is penetrated by a liquid electrolyte. The present disclosure relates to improved lithium-containing electrodes for lithium-containing electrochemical cells (e.g., lithium-ion batteries). It has been found that, as further described below, ceramic particles disposed on and / or within the lithium-containing electrode can improve the performance of the electrochemical cell. More specifically, the ceramic particles can improve various electromechanical properties of the SEI layer (e.g., ion transport, stiffness), and promote smooth deposition of lithium, thereby resulting in higher coulombic efficiency, rate performance, and fast charging capability.

[0128] Provided herein are electrochemical cells for use in batteries (e.g., lithium-ion batteries) or as capacitors. For example, in Figure 1 An exemplary and schematic illustration of an electrochemical cell (also referred to as a lithium-ion battery or battery) 10 is shown in FIG. The electrochemical cell 10 includes a negative electrode 22 (also referred to as a negative electrode layer 22), a positive electrode 24 (also referred to as a positive electrode layer 24), and a separator 26 (e.g., a microporous polymer separator) disposed between the two electrodes 22, 24. As further described below, the negative electrode 22 may also include ceramic particles 55. The space between the negative electrode 22 and the positive electrode 24 (e.g., the separator 26) may be filled with an electrolyte 30. If pores exist inside the negative electrode 22 and the positive electrode 24, the pores may also be filled with the electrolyte 30. The electrolyte 30 may impregnate, permeate, or wet the respective surfaces of the negative electrode 22, the positive electrode 24, and the porous separator 26 and fill their respective pores. The negative electrode current collector 32 may be located at or near the negative electrode 22, and the positive electrode current collector 34 may be located at or near the positive electrode 24. The negative electrode current collector 32 and the positive electrode current collector 34 collect and move free electrons to and from the external circuit 40, respectively. The interruptible external circuit 40 and the load device 42 connect the negative electrode 22 (through its current collector 32) and the positive electrode 24 (through its current collector 34). The negative electrode 22, the positive electrode 24 and the separator 26 can each also contain an electrolyte 30 capable of conducting lithium ions. The separator 26 acts as both an electrical insulator and a mechanical support by being sandwiched between the negative electrode 22 and the positive electrode 24 to prevent physical contact and thereby prevent short circuits. In addition to providing a physical barrier between the two electrodes 22 and 24, the separator 26 can also provide a path of least resistance for the internal passage of lithium ions (and related anions) to facilitate the functioning of the battery 10. During the lithium ion cycling process, the separator 26 also contains the electrolyte solution in a network of open pores to facilitate the functioning of the battery 10.

[0129] The battery 10 can generate current during discharge by a reversible electrochemical reaction that occurs when the external circuit 40 (to connect the negative electrode 22 and the positive electrode 24) is closed when the negative electrode 22 contains a relatively larger amount of intercalated lithium. The chemical potential difference between the positive electrode 24 and the negative electrode 22 will be driven toward the positive electrode 24 via the external circuit 40 by the electrons generated by the oxidation of the intercalated lithium at the negative electrode 22. The lithium ions also generated at the negative electrode are transferred toward the positive electrode 24 through the electrolyte 30 and the separator 26 at the same time. The electrons flow through the external circuit 40 and the lithium ions migrate through the separator 26 in the electrolyte 30 to form intercalated lithium at the positive electrode 24. The current through the external circuit 40 can be utilized and directed through the load device 42 until the intercalated lithium in the negative electrode 22 is exhausted and the capacity of the lithium ion battery 10 is reduced.

[0130] The lithium-ion battery 10 can be charged or re-powered / re-energized at any time by connecting an external power source to the lithium-ion battery 10 to reverse the electrochemical reactions that occur during the battery discharge process. Connecting the external power source to the lithium-ion battery 10 forces the intercalated lithium to undergo a separate non-spontaneous oxidation at the positive electrode 24 to produce electrons and lithium ions. The electrons flowing back toward the negative electrode 22 through the external circuit 40 and the lithium ions carried by the electrolyte 30 through the separator 26 back to the negative electrode 22 are recombined at the negative electrode 22 and replenished with intercalated lithium for consumption during the next battery discharge event. Thus, a complete discharge event followed by a complete charging event is considered to be a cycle, in which lithium ions circulate between the positive electrode 24 and the negative electrode 22. The external power source that can be used to charge the lithium-ion battery 10 can vary depending on the size, construction, and specific end use of the lithium-ion battery 10. Some notable and exemplary external power sources include, but are not limited to, AC wall outlets and automobile alternators.

[0131] In many battery configurations, the negative electrode current collector 32, the negative electrode 22, the separator 26, the positive electrode 24, and the positive electrode current collector 34 are each prepared as relatively thin layers (e.g., a few microns or a millimeter or less in thickness) and assembled in layers connected in an electrically parallel arrangement to provide a suitable energy package. The negative electrode current collector 32 and the positive electrode current collector 34 collect and move free electrons to and from the external circuit 40, respectively.

[0132] In addition, the battery 10 may include a variety of other components that, although not depicted herein, are known to those skilled in the art. For example, as a non-limiting example, the lithium-ion battery 10 may include a housing, gaskets, end caps, tabs, battery terminals, and any other conventional components or materials that may be located within the battery 10 (including between or around the negative electrode 22, the positive electrode 24, and / or the separator 26). Figure 1 The battery 10 shown in FIG. 1 includes a liquid electrolyte 30 and illustrates a representative battery operating concept.

[0133] As described above, the size and shape of the lithium-ion battery pack 10 can vary depending on the specific application for which it is designed. Battery-powered vehicles and handheld consumer electronic devices, for example, are two examples in which the battery pack 10 is most likely to be designed to different size, capacity, and power output specifications. The battery pack 10 can also be connected in series or parallel with other similar lithium-ion cells or batteries to produce a greater voltage output and power density if required by the load device 42.

[0134] Thus, the battery pack 10 can generate an electric current toward a load device 42 that is operably connected to the external circuit 40. The load device 42 can be powered in whole or in part by the current that passes through the external circuit 40 when the lithium-ion battery pack 10 is discharged. Although the load device 42 can be any number of known electric devices, as non-limiting examples, a small number of specific examples of power-consuming load devices include electric motors for hybrid or all-electric vehicles, laptop computers, tablet computers, mobile phones, and cordless power tools or appliances. The load device 42 can also be a power generation device that charges the battery pack 10 for the purpose of storing energy.

[0135] The present technology relates to improved electrochemical cells, particularly lithium ion batteries. In various cases, such batteries are used in vehicle or automotive transportation applications (e.g., motorcycles, boats, tractors, buses, motorbikes, trailers, campers, and tanks). However, the present technology can also be used in a variety of other industries and applications, including, as non-limiting examples, aerospace parts, consumer products, devices, buildings (e.g., houses, offices, storerooms, and warehouses), office equipment and furniture, and industrial equipment machinery, agricultural or farm equipment, or heavy machinery.

[0136] A. Negative electrode containing ceramic particles

[0137] In various aspects, provided herein are lithium metal electrodes, such as negative electrode 22 ( Figure 1 ). The negative electrode 22 comprises an electroactive material (also referred to as a first electroactive material) as a lithium host material capable of acting as a negative terminal of a lithium-ion battery pack. The first electroactive material may be formed of metallic lithium or include metallic lithium. It is contemplated herein that the first electroactive material may include or consist of all metallic lithium (e.g., 100% by weight of lithium based on the total weight of the first electroactive material). In addition or alternatively, the first electroactive material may include a lithium silicon alloy, a lithium aluminum alloy, a lithium indium alloy, a lithium tin alloy, or a combination thereof. The negative electrode 22 may also optionally include one or more of graphite, activated carbon, carbon black, hard carbon, soft carbon, graphene, silicon, tin oxide, aluminum, indium, zinc, germanium, silicon oxide, titanium oxide, lithium titanate, and combinations thereof, such as silicon mixed with graphite. Non-limiting examples of silicon-containing electroactive materials include silicon (amorphous or crystalline) or silicon-containing binary and ternary alloys, such as Si-Sn, SiSnFe, SiSnAl, SiFeCo, and the like. In other variations, negative electrode 22 may be a metal film or foil, such as a lithium metal film or a lithium-containing foil.

[0138] An enlarged exemplary schematic diagram of the negative electrode 22 including ceramic particles 55 is shown in Figure 2A In. Figure 2AIn the embodiment, the negative electrode configuration 20a includes a lithium-containing electrode (e.g., negative electrode 22), which includes a first surface 23 (e.g., a first lithium-containing surface), and a second surface 25 (e.g., a second lithium-containing surface), and the second surface 25 is adjacent to or disposed on the current collector 32.

[0139] In any embodiment, the ceramic particles 55 may include lithium lanthanum zirconium oxide (LLZO) particles, aluminum oxide (Al2O3 or aluminum oxide) particles, zirconium oxide particles (ZrO2 or zirconium dioxide), or a combination or mixture thereof. In some embodiments, only LLZO particles are present. In other embodiments, only aluminum oxide particles are present. In other embodiments, only zirconium oxide particles are present. In other embodiments, LLZO particles and aluminum oxide particles are present, or LLZO particles and zirconium oxide particles are present, or aluminum oxide particles and zirconium oxide particles are present, or LLZO particles, aluminum oxide particles, and zirconium oxide particles are present.

[0140] In any embodiment, the LLZO particles can be doped with any combination of suitable dopants, such as Al, Ca, Mg, Sr, Ba, Be, Ge, Ta, and / or Nb. For example, the LLZO particles can be doped with Al or Ge on the Li site, Ca on the La site, and Ta or Nb on the Zr site to produce any combination of 0 to 1 vacancies on the Li site per formula unit. LLZO can be doped to maintain a cubic form, depending on the temperature. In any embodiment, the LLZO particles can correspond to one or more of the following formulas: Li (7-3y) Al y La3Zr2O 12 , where 0 ≤ y ≤ 2 / 3; and Li 7+x-3y-z La 3-x (M) x (N) y Zr 2-z (Q) z O 12 , wherein M is Ca, Ba, Mg or Sr; N is Al or (3 / 4)Ge; Q is Ta or Nb; 0 ≤ x ≤ 1; 0 ≤ y ≤ 2 / 3; 0 ≤ z ≤ 2; and 5 ≤ (7 + x - 3y - z) ≤ 7. Examples of the composition of LLZO particles include, but are not limited to, Li7La3Zr2O 12 , Li 6.25 Al 0.25 La3Zr2O 12 , Li 6.5 LqCy 1.5 Ta 0.5 O 12 or a combination thereof.

[0141] Alumina particles and zirconia particles may exist in any phase. For example, zirconia particles may exist in a monoclinic phase, a tetragonal phase, a cubic phase, or a combination thereof. In any embodiment, the alumina particles may include crystallized α-Al2O3 particles, β-Al2O3 particles, γ-Al2O3 particles, η-Al2O3 particles, θ-Al2O3 particles, κ-Al2O3 particles, χ-Al2O3 particles, σ-Al2O3 particles, or a combination thereof. In some embodiments, the alumina particles include α-Al2O3 particles.

[0142] In some embodiments, the ceramic particles can be pretreated to improve lithium metal wettability before being applied to the first surface 23 of the negative electrode 22. For example, the ceramic particles can be pretreated with a coating, such as the Li3PO4 coating described in U.S. Patent Application Serial No. 16 / 791,158, the entire contents of which are incorporated herein by reference. Additionally or alternatively, the ceramic particles can be pretreated via atomic layer deposition to apply an alumina or titania coating. Additionally or alternatively, the ceramic particles can be pretreated to reduce the size of the ceramic particles, such as by grinding or milling the ceramic particles in a ball mill.

[0143] In any embodiment, if Figure 2A As shown in , the ceramic particles 55 can be present in the form of a ceramic layer 50 adjacent to or disposed on at least a portion of the first surface 23 of the negative electrode 22. In such an embodiment, when present in the battery 10, the ceramic layer 50 can be disposed between the negative electrode 22 and the separator 26. In various aspects, the ceramic layer 50 can be substantially continuous or can be substantially discontinuous. The thickness of the ceramic coating 50 can be greater than or equal to about 100 nm, greater than or equal to about 500 nm, greater than or equal to about 1 μm, greater than or equal to about 10 μm, greater than or equal to about 25 μm, greater than or equal to about 50 μm, greater than or equal to about 75 μm, greater than or equal to about 100 μm, greater than or equal to about 200 μm, or about 400 μm; or about 100 nm to about 400 μm, about 500 nm to about 200 μm, about 1 μm to about 100 μm, or about 10 μm to about 75 μm. In any embodiment, the ceramic layer 50 can be bonded to the first surface 23 via electrostatic interactions. Additionally or alternatively, when the LLZO particles are exposed to air, Li2CO3 and LiOH can form and promote the attachment of ceramic particles 55 to the first surface 23.

[0144] Additionally or alternatively, Figure 2BAs shown in FIG. 5 , in the negative electrode configuration 20 b, the ceramic particles 55 may be embedded within, embedded onto, and / or embedded in the first surface 23 of the negative electrode 22. In such an embodiment, a portion of the ceramic particles 55 may be exposed at the first surface 23 of the negative electrode 22. Although not shown, it is contemplated herein that the ceramic particles 55 may be present both in the form of a ceramic layer 50 and embedded within the first surface 23 of the negative electrode 22. When present, the LLZO particles may be present in an amount greater than or equal to about 0.5 g / cm 2 , greater than or equal to approximately 1 g / cm 2 , greater than or equal to approximately 5 g / cm 2 , greater than or equal to approximately 10 g / cm 2 , greater than or equal to approximately 20 g / cm 2 , greater than or equal to approximately 30 g / cm 2 , greater than or equal to approximately 40 g / cm 2 , or about 50 g / cm 2 , or about 0.5 g / cm 2 Up to about 50 g / cm 2 , about 0.5 g / cm 2 Up to about 40 g / cm 2 , about 0.5 g / cm 2 Up to about 30 g / cm 2 , about 1 g / cm 2 Up to about 20 g / cm 2 , about 1 g / cm 2 Up to about 10 g / cm 2 , or about 3 g / cm 2 Up to about 9 g / cm 2 The aluminum oxide particles, when present, may be present on the negative electrode 22 (e.g., in the ceramic layer 50 or embedded in the first surface 23) in an amount greater than or equal to about 0.4 g / cm 2 , greater than or equal to approximately 1 g / cm 2 , greater than or equal to approximately 5 g / cm 2 , greater than or equal to approximately 10 g / cm 2 , greater than or equal to approximately 20 g / cm 2 , greater than or equal to approximately 30 g / cm 2 , or about 40 g / cm 2 , or about 0.4 g / cm 2 Up to about 40 g / cm 2 , about 0.4 g / cm 2 Up to about 30 g / cm2 , about 1 g / cm 2 Up to about 20 g / cm 2 , about 1 g / cm 2 Up to about 10 g / cm 2 , or about 2 g / cm 2 Up to about 8 g / cm 2 The zirconium oxide particles, when present, may be present on the negative electrode 22 (e.g., in the ceramic layer 50 or embedded in the first surface 23) in an amount greater than or equal to about 0.5 g / cm 2 , greater than or equal to approximately 1 g / cm 2 , greater than or equal to approximately 5 g / cm 2 , greater than or equal to approximately 10 g / cm 2 , greater than or equal to approximately 20 g / cm 2 , greater than or equal to approximately 30 g / cm 2 , greater than or equal to approximately 40 g / cm 2 , or about 50g / cm 2 , or about 0.5 g / cm 2 Up to about 50 g / cm 2 , about 0.5 g / cm 2 Up to about 40 g / cm 2 , about 0.5 g / cm 2 Up to about 30 g / cm 2 , about 1 g / cm 2 Up to about 20 g / cm 2 , about 1 g / cm 2 Up to about 10 g / cm 2 , or about 3 g / cm 2 Up to about 9 g / cm 2 An amount of is present on negative electrode 22 (eg, in ceramic layer 50 or embedded in first surface 23 ).

[0145] The LLZO particles, alumina particles, and zirconia particles can each have an average particle size of greater than or equal to about 50 nm, greater than or equal to about 100 nm, greater than or equal to about 500 nm, greater than or equal to about 750 nm, greater than or equal to about 1 µm, greater than or equal to about 5 µm, greater than or equal to about 10 µm, greater than or equal to about 15 µm, greater than or equal to about 20 µm, greater than or equal to about 30 µm, or about 50 µm; or any average particle size from about 50 nm to about 50 µm, from about 100 nm to about 20 µm, from about 500 nm to about 15 µm, or from about 1 µm to about 10 µm.

[0146] As described above, during the electrochemical cell cycling process, the SEI layer can be formed on the negative electrode. Without being bound by theory, it is believed that the embedded ceramic particles (e.g., LLZO particles and / or alumina particles) can improve the ion transport of lithium ions through the SEI layer and the mechanical robustness of the SEI layer, which can lead to smoother lithium metal stripping and plating, thereby improving the coulombic efficiency. In addition, without being bound by theory, it is believed that the ceramic particles (e.g., LLZO particles and / or alumina particles) embedded in or on the first surface of the negative electrode can increase the surface area of ​​the lithium-containing negative electrode that can be used for stripping and plating without additional exposure to the electrolyte, thereby leading to improved rate performance and fast charging capability. In addition, as the electrochemical cell operates and the SEI layer is formed on the surface (e.g., first surface 23) of the negative electrode (e.g., negative electrode 22), the ceramic particles can become embedded in the SEI layer. Without being bound by theory, it is believed that the ceramic particles embedded in the SEI layer can advantageously promote uniform lithium ion flow distribution, reduce SEI resistance, increase SEI stiffness, and remove hydrofluoric acid (HF). Hydrofluoric acid is highly corrosive and may be produced in the electrochemical cell 10 during the decomposition of the electrolyte. The resulting HF may increase the acidity of the liquid electrolyte 30, which may lead to corrosion of the positive electrode and / or current collectors 32, 34. HF may also decompose the existing SEI layer, resulting in more electrolyte consumption. Therefore, by acting as an HF scavenger, the ceramic particles can help reduce corrosion and degradation of various components of the battery 10.

[0147] Additionally or alternatively, the ceramic particles 55 may also include a binder 60. Figure 2C and 2D As shown in , the binder 60 may be present in the form of discrete particles or fragments in the negative electrode configuration 20c, 20d. In addition or alternatively, the binder 60 may be present in the form of a more continuous phase in which the ceramic particles 55 are dispersed. Examples of suitable binders 60 include, but are not limited to, polyacrylonitrile (PAN), polyimide, polyvinyl pyrrolidone (PVP), polyvinyl butyral, polyvinyl acetate, methyl cellulose, ethyl cellulose, polyacrylates, polyurethanes, polyethylene glycols, acrylic compounds, polystyrene, polyvinyl alcohol, polymethyl methacrylate, polybutyl methacrylate, and combinations thereof. In any embodiment, the binder 60 may coat at least a portion of the surface of the ceramic particles 55, or the binder 60 may substantially coat the entire surface of the ceramic particles 55. In some embodiments, the binder 60 should only partially coat the surface of the ceramic particles 55, or dissolve in situ (e.g., when in contact with the electrolyte), and not coat the entire surface of the ceramic particles 55, so as not to make the ceramic particles 55 insulating and inert.

[0148] If present, binder 60 can be present in an amount of less than or equal to about 40 wt %, less than or equal to about 30 wt %, less than or equal to about 20 wt %, less than or equal to about 10 wt %, less than or equal to about 5 wt %, or about 1 wt %; or from about 1 wt % to about 40 wt %, from about 1 wt % to about 30 wt %, from about 5 wt % to about 30 wt %, or from about 1 wt % to about 10 wt %, based on the total weight of the ceramic particles and the binder (e.g., the total weight of the ceramic coating 50). In alternative embodiments, the binder is not present with the ceramic particles 55.

[0149] In some embodiments, negative electrode 22 can have a small amount of passivation layer (less than 20%, less than 10%, less than 5% of the original passivation layer) or essentially no (less than 1%) passivation layer present on first surface 23, such as a passivation layer between first surface 23 and ceramic layer 50.

[0150] Additionally, the negative electrode 22 may optionally include a conductive material and / or a polymer binder, for example, in embodiments where the negative electrode 22 is not 100% lithium metal. Examples of conductive materials include, but are not limited to, carbon black, graphite, acetylene black (e.g., KETCHEN TM Black or DENKA TM Black), carbon nanotubes, carbon fibers, carbon nanofibers, graphene, graphene nanosheets, graphene oxide, nitrogen-doped carbon, metal powders (e.g., copper, nickel, steel), liquid metals (e.g., Ga, GaInSn), conductive polymers (e.g., including polyaniline, polythiophene, polyacetylene, polypyrrole, etc.) and combinations thereof. Such conductive materials in particle form may have a circular geometry or an axial geometry as described above. The term "graphene nanosheet" as used herein refers to a nanosheet or stack of graphene layers.

[0151] The term "polymer binder" as used herein includes polymer precursors for forming polymer binders, such as monomers or monomer systems that can form any of the polymer binders disclosed above. Examples of suitable polymer binders include, but are not limited to, polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), ethylene propylene diene monomer (EPDM) rubber or carboxymethyl cellulose (CMC), nitrile rubber (NBR), styrene-butadiene rubber (SBR), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), poly (acrylic acid) PAA, polyimide, polyamide, sodium alginate, lithium alginate, and combinations thereof. In some embodiments, the polymer binder may be a non-aqueous solvent-based polymer or a water-based polymer. In particular, the polymer binder may be a non-aqueous solvent-based polymer, which may exhibit lower capacity decay, provide a more robust mechanical network and improved mechanical properties to more effectively cope with silicon particle expansion, and have good chemical resistance and heat resistance. For example, the polymer binder may include polyimide, polyamide, polyacrylonitrile, polyacrylic acid, salts of polyacrylic acid (e.g., potassium, sodium, lithium), polyacrylamide, polyvinyl alcohol, carboxymethyl cellulose, or combinations thereof. The first electroactive material may be mixed with a conductive material and at least one polymer binder. For example, the first electroactive material and the optional conductive material may be slurry cast with such a binder and applied to a current collector. The polymer binder may play multiple roles in the electrode, including: (i) enabling electronic and ionic conductivity of the composite electrode, (ii) providing electrode integrity, such as the integrity of the electrode and its components, and its adhesion to the current collector, and (iii) participating in the formation of a solid electrolyte interface phase (SEI), which plays an important role because the kinetics of lithium insertion are primarily determined by the SEI.

[0152] In various aspects, the first electroactive material may be present in the negative electrode in an amount of about 50% to about 100% by weight, about 50% to about 98% by weight, about 60% to about 95% by weight, about 60% to about 95% by weight, or about 60% to about 80% by weight, based on the total weight of the negative electrode. Additionally or alternatively, the conductive material may be present in the negative electrode in an amount of about 0.2% to about 25% by weight, about 1% to about 25% by weight, about 2% to about 20% by weight, about 5% to about 15% by weight, or about 2% to about 10% by weight, based on the total weight of the negative electrode. Additionally or alternatively, the polymer binder may be present in the negative electrode in an amount of about 0.5% to about 30% by weight, about 1% to about 25% by weight, about 3% to about 20% by weight, or about 5% to about 15% by weight, based on the total weight of the negative electrode.

[0153] B. Positive electrode

[0154] The positive electrode 24 can be formed of a second electroactive material that can sufficiently perform lithium intercalation and deintercalation while serving as the positive terminal of the lithium-ion battery pack 10. The positive electrode 24 can also include a polymeric binder material to structurally strengthen the lithium-based active material and the conductive material. An exemplary common type of known material that can be used to form the positive electrode 24 is layered lithium transition metal oxide. For example, in certain embodiments, the positive electrode 24 can include Li (1+x) Mn2O4, where 0.1 ≤ x ≤ 1; LiMn (2-x) Ni x O4, where 0 ≤ x ≤ 0.5; LiCoO2; Li(Ni x Mn y Co z )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, and x + y + z = 1; LiNi (1-x-y) Co x M y O2, where 0 < x < 0.2, y < 0.2, and M is Al, Mg, or Ti; LiFePO4, LiMn 2-x Fe x PO4, where 0 < x < 0.3; LiNiCoAlO2; LiMPO4, where M is at least one of Fe, Ni, Co, and Mn; Li(Ni x Mn y Co z Al p )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ P ≤ 1, x + y + z + p = 1 (NCMA); LiNiMnCoO2; Li2Fe x M 1-x PO4 (M = Mn and / or Ni, 0 ≤ x ≤ 1); LiMn2O4; LiFeSiO4; LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622), LiMnO2 (LMO), activated carbon, sulfur (e.g., greater than 60 wt% based on the total weight of the positive electrode), or a combination thereof.

[0155] In some variations, the second electroactive material can be mixed with an electronically conductive material that provides an electronically conductive path as described herein and / or at least one polymer binder material that improves the structural integrity of the electrode as described herein. For example, the second electroactive material and the electronically conductive material or the conductive material can be slurry cast with such a binder, such as polyvinylidene fluoride (PVdF), polytetrafluoroethylene (PTFE), ethylene propylene diene monomer (EPDM) rubber or carboxymethyl cellulose (CMC), nitrile rubber (NBR), styrene-butadiene rubber (SBR), lithium polyacrylate (LiPAA), sodium polyacrylate (NaPAA), poly (acrylic acid) PAA, polyimide, polyamide, sodium alginate or lithium alginate and applied to the current collector.

[0156] C. Current Collector

[0157] The positive electrode current collector 34 may be formed of aluminum (Al) or any other suitable conductive material known to those skilled in the art. The negative electrode current collector 32 may include a metal containing copper, nickel or an alloy thereof, stainless steel or other suitable conductive materials known to those skilled in the art. In some aspects, the positive electrode current collector 34 and / or the negative electrode current collector 32 may be in the form of a foil, a slit mesh and / or a woven mesh.

[0158] D. Electrolytes

[0159] The positive electrode 24, the negative electrode 22, and the separator 26 can each contain within their pores an electrolyte solution or system 30 capable of conducting lithium ions between the negative electrode 22 and the positive electrode 24. Any suitable electrolyte 30 capable of conducting lithium ions between the negative electrode 22 and the positive electrode 24 can be used in the lithium ion battery 10, whether in solid, liquid, or gel form. In certain aspects, the electrolyte 30 can be a non-aqueous liquid electrolyte solution comprising a lithium salt dissolved in an organic solvent or organic solvent mixture. A variety of conventional non-aqueous liquid electrolyte 30 solutions can be used in the lithium ion battery 10.

[0160] In some aspects, the electrolyte 30 can be a non-aqueous liquid electrolyte solution comprising one or more lithium salts dissolved in an organic solvent or an organic solvent mixture. For example, a non-limiting list of lithium salts that can be dissolved in an organic solvent to form a non-aqueous liquid electrolyte solution includes lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrachloroaluminate (LiAlCl4), lithium iodide (LiI), lithium bromide (LiBr), lithium thiocyanate (LiSCN), lithium tetrafluoroborate (LiBF4), lithium tetraphenylborate (LiB(C6H5)4), lithium bis(oxalato)borate (LiB(C2O4)2) (LiBO B), lithium difluorooxalatoborate (LiBF2(C2O4)), lithium hexafluoroarsenate (LiAsF6), lithium trifluoromethanesulfonate (LiCF3SO3), lithium bis(trifluoromethanesulfonyl)imide (LiN(CF3SO2)2), lithium bis(fluorosulfonyl)imide (LiN(FSO2)2) (LiSFI), lithium (triethylene glycol dimethyl ether) bis(trifluoromethanesulfonyl)imide (Li(G3)(TFSI)), lithium bis(trifluoromethanesulfonyl)azanide (LiTFSA) and combinations thereof.

[0161] These and other similar lithium salts can be dissolved in various non-aqueous aprotic organic solvents, including, but not limited to, various alkyl carbonates, such as cyclic carbonates (e.g., ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), fluoroethylene carbonate (FEC)), linear carbonates (e.g., dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC)), aliphatic carboxylates (e.g., methyl formate, methyl acetate, methyl propionate), γ-lactones (e.g., γ-butyrolactone, γ-valerolactone), chain structure ethers (e.g., 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane), cyclic ethers (e.g., tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane), sulfur compounds (e.g., sulfolane), acetonitrile, and combinations thereof. The one or more salts can be present in the electrolyte at a concentration of about 1 M to about 4 M, for example, about 1 M, about 1 M to 2 M, or about 3 M to about 4 M.

[0162] Additionally or alternatively, the electrolyte may include additives that can, for example, improve the temperature and voltage stability of the electrochemical cell materials (e.g., electrolyte 30, negative electrode 22, and positive electrode 24). Examples of suitable additives include, but are not limited to, for example, ethylene carbonate, ethylene carbonate-ethylene ester, propane sulfonate, and combinations thereof. Other additives may include diluents that do not coordinate with lithium ions but can reduce viscosity, such as bis(2,2,2-trifluoroethyl) ether (BTFE), and flame retardants, such as triethyl phosphate.

[0163] E. Diaphragm

[0164] The diaphragm 26 may include, for example, a microporous polymer diaphragm comprising a polyolefin or PTFE. The polyolefin may be a homopolymer (derived from a single monomer component) or a heteropolymer (derived from more than one monomer component), which may be linear or branched. If the heteropolymer is derived from two monomer components, the polyolefin may have any copolymer chain arrangement, including those of block copolymers or random copolymers. Similarly, if the polyolefin is a heteropolymer derived from more than two monomer components, it may also be a block copolymer or a random copolymer. In some aspects, the polyolefin may be polyethylene (PE), polypropylene (PP), or a blend of PE and PP, or a multilayer structured porous membrane of PE and / or PP. Commercially available polyolefin porous diaphragms include CELGARD ® available from Celgard LLC. ® 2500 (a single-layer polypropylene diaphragm) and CELGARD ® 2325 (a three-layer polypropylene / polyethylene / polypropylene separator).

[0165] In some aspects, the diaphragm 26 may further include one or more of a ceramic coating and a heat-resistant material coating. The ceramic coating and / or the heat-resistant material coating may be disposed on one or more surfaces of the diaphragm 26. The material forming the ceramic layer may be selected from: alumina (Al2O3), silicon dioxide (SiO2) and combinations thereof. The heat-resistant material may be selected from: Nomex, Aramid and combinations thereof.

[0166] When the diaphragm 26 is a microporous polymer diaphragm, it can be a single layer or a multilayer laminate, which can be manufactured by a dry or wet process. For example, in some cases, a single polyolefin layer can form the entire diaphragm 26. In other aspects, the diaphragm 26 can be a fiber membrane having a large number of pores extending between opposing surfaces and having an average thickness of, for example, less than 1 mm. However, as another example, a plurality of discrete layers of similar or dissimilar polyolefins can be assembled to form a microporous polymer diaphragm 26. In addition to polyolefins, the diaphragm 26 can also include other polymers, such as but not limited to polyethylene terephthalate (PET), polyvinylidene fluoride (PVdF), polyamide, polyimide, poly (amide-imide) copolymer, polyetherimide and / or cellulose, or any other material suitable for generating a desired porous structure. A polyolefin layer in the form of a fiber layer and any other optional polymer layer can be further included in the diaphragm 26 to help provide the diaphragm 26 with appropriate structural properties and porosity properties. In some aspects, the separator 26 may also be mixed with a ceramic material, or its surface may be coated with a ceramic material. For example, the ceramic coating may include aluminum oxide (Al2O3), silicon dioxide (SiO2), titanium dioxide (TiO2), or a combination thereof. Various commercially available polymers and commercial products for forming the separator 26 are contemplated, as well as many manufacturing methods that can be used to make such a microporous polymer separator 26.

[0167] In various aspects, the membrane may be replaced by a solid-state electrolyte ("SSE") (not shown) that acts as both an electrolyte and a separator. Figure 1 The SSE may be disposed between the positive electrode 24 and the negative electrode 22. The SSE facilitates the transfer of lithium ions while mechanically separating the negative electrode 22 from the positive electrode 24 and providing electrical insulation therebetween. As non-limiting examples, the SSE may include LiTi2(PO4)3, LiGe2(PO4)3, Li7La3Zr2O 12 , Li 3x La 2 / 3-x TiO3, Li3PO4, Li3N, Li4GeS4, Li 10 GeP2S 12 , Li2S-P2S5, Li6PS5Cl, Li6PS5Br, Li6PS5I, Li3OCl, Li 2.99 Ba 0.005 C10 or a combination thereof.

[0168] Now refer to Figure 3 , electrochemical cell 10 (such as Figure 1 ) can be combined with one or more other electrochemical cells to produce a lithium-ion battery pack 400. Figure 3The lithium-ion battery pack 400 shown in the figure includes a plurality of rectangular electrochemical cells 410. Any number of electrochemical cells 410 from 5 to 150 can be stacked side-by-side in a modular configuration and connected in series or in parallel to form a lithium-ion battery pack 400, such as for a vehicle powertrain. The lithium-ion battery pack 400 can be further connected in series or in parallel with other similarly constructed lithium-ion battery packs to form a lithium-ion battery pack that exhibits the voltage and current capacity required for a particular application (e.g., for a vehicle). It should be understood that Figure 3 The lithium-ion battery 400 shown in FIG. 4 is merely a schematic illustration and is not intended to convey the relative sizes of any components of the electrochemical cell 410 or to limit the various structural configurations that the lithium-ion battery 400 may have. Although such a situation is explicitly described, Figure 3 Various structural modifications of the lithium-ion battery pack 400 shown in FIG. 4 are possible.

[0169] Each electrochemical cell 410 includes a negative electrode 412, a positive electrode 414, and a separator 416 located between the two electrodes 412, 414. One or more of the negative electrodes 412 may contain ceramic particles 55 (not shown) as described herein. The negative electrode 412, the positive electrode 414, and the separator 416 are each impregnated, permeated, or wetted with a liquid electrolyte (e.g., electrolyte 30) capable of transporting lithium ions. A negative electrode current collector 420 including a negative polarity tab 444 is located between the negative electrodes 412 of adjacent electrochemical cells 410. Similarly, a positive electrode current collector 422 including a positive polarity tab 446 is located between adjacent positive electrodes 424. The negative polarity tab 444 is electrically coupled to the negative terminal 448, and the positive polarity tab 446 is electrically coupled to the positive terminal 450. The applied compressive forces generally press the current collectors 420 , 422 against the electrodes 412 , 414 and the electrodes 412 , 414 against the separator 416 to achieve intimate interfacial contact between the several contact components of each electrochemical cell 410 .

[0170] The battery pack 400 may include more than two pairs of positive and negative electrodes 412, 414. In one form, the battery pack 400 may include 15-60 pairs of positive and negative electrodes 412, 414. Figure 3 The battery pack 400 depicted in FIG. 4 is composed of a plurality of discrete electrodes 412, 414 and a separator 416, but other arrangements are certainly possible. For example, instead of discrete separators 416, the positive and negative electrodes 412, 414 can be separated from each other by winding or interweaving a single continuous separator sheet between the positive and negative electrodes 412, 414. In another example, the battery pack 400 can include continuous and sequentially stacked positive electrode, separator, and negative electrode sheets that are folded or rolled together to form a "jelly roll".

[0171] The negative and positive terminals 448, 450 of the lithium-ion battery pack 400 are connected to an electrical device 452 as part of an interruptible circuit 454, which is established between the negative electrode 412 and the positive electrode 414 of many electrochemical cells 410. The electrical device 452 may include an electrical load or a power generation device. An electrical load is an electrical consumption device that is fully or partially powered by the lithium-ion battery pack 400. In contrast, a power generation device is a device that charges or repowers the lithium-ion battery pack 400 by an applied external voltage. In some cases, the electrical load and the power generation device may be the same device. For example, the electrical device 452 may be an electric motor for a hybrid electric vehicle or an extended-range electric vehicle, which is designed to draw current from the lithium-ion battery pack 400 during acceleration and provide regenerative current to the lithium-ion battery pack 400 during deceleration. The electrical load and the power generation device may also be different devices. For example, the electrical load may be an electric motor for a hybrid electric vehicle or an extended-range electric vehicle, and the power generation device may be an AC wall outlet, an internal combustion engine, and / or a vehicle alternator.

[0172] When the negative electrode 412 contains a sufficient amount of intercalated lithium (i.e., during discharge), when the interruptible circuit 454 is closed to connect the negative terminal 448 and the positive terminal 450, the lithium ion battery 400 can provide a usable current to the electrical device 452 through the reversible electrochemical reactions occurring in the electrochemical cell 410. When the negative electrode 412 is depleted of intercalated lithium and the capacity of the electrochemical cell 410 is exhausted, the lithium ion battery 400 can be charged or repowered by applying an external voltage from the electrical device 452 to the electrochemical cell 410 to reverse the electrochemical reactions occurring during discharge.

[0173] Although not depicted in the drawings, the lithium-ion battery 400 may include a variety of other components. For example, the lithium-ion battery 400 may include a housing, a gasket, an end cap, and any other desirable components or materials that may be located between or around the electrochemical cells 410 for performance-related purposes or other practical purposes. For example, the lithium-ion battery 400 may be enclosed in a housing (not shown). The housing may include a metal such as aluminum or steel, or the housing may include a film pouch material having a plurality of laminated layers. The electrochemical cells 10, 400 contemplated to be formed herein may be soft pack cells, button cells, or another full electrochemical cell having a cylindrical form or a wound prism form.

[0174] II. Method for preparing a lithium-containing electrode comprising ceramic particles

[0175] Also provided herein is a method for preparing a lithium-containing electrode, such as negative electrode 22. The method includes applying ceramic particles (e.g., ceramic particles 55) to a surface (e.g., first surface 23) of a negative electrode (e.g., negative electrode 22). Applying the ceramic particles may include any suitable dry casting / coating or slurry casting / coating method. Such methods include, but are not limited to, spray coating, knife-over-edge coating, slot die coating, direct gravure coating, and micro-gravure coating, such as described in J. Park et al., Int'l J. of Precision Eng. And Manf., 17,4 (2016), pp. 1-14. Other application methods include rod coating, drop casting, spin coating, doctor blading, and dip coating. As described above, the ceramic particles or powders may be pretreated before being applied to the negative electrode; thus, the methods provided herein may include one or more of the above-mentioned pretreatment steps.

[0176] Figure 4A An example of dry casting is shown in Figure 4A In the embodiment, when the negative electrode 22 disposed on the current collector 32 is conveyed via the roller 74, the ceramic particles 55 can be sprayed onto the first surface 23 of the negative electrode 22 via the spraying device 70 and form a ceramic layer 50. Examples of suitable spraying devices 70 include, but are not limited to, a friction spray gun, a corona spray gun, or an electrostatic spray gun. It is contemplated herein that the ceramic powder can be suspended and sprayed onto the first surface 23 via the spraying device 70. In any embodiment, the spraying device 70 can impart an electric charge (e.g., a positive charge) to the ceramic particles 55 to improve adhesion to the negative electrode 22. The binder 60 can optionally be sprayed together with the ceramic particles 55 via the spraying device 70.

[0177] Figure 4C An example of slurry casting is shown in . For slurry casting, ceramic particles 55 and optional binder 60 can be mixed with a solvent to form a slurry. Non-limiting examples of suitable solvents include xylene, hexane, methyl ethyl ketone, acetone, toluene, dimethylformamide, aromatic hydrocarbons, N-methyl-2-pyrrolidone (NMP), and combinations thereof. Figure 4CIn the embodiment of the present invention, when the negative electrode 22 disposed on the current collector 32 is conveyed via the roller 74, the slurry containing the ceramic particles 55 and the optional binder 60 can be applied to the first surface 23 of the negative electrode 22 via the slurry applying device 80. Examples of the slurry applying device 80 include, but are not limited to, a doctor blade, a slot die, direct gravure coating, or micro gravure coating. After the slurry is applied to the negative electrode 22, the method may further include a drying or volatilization step to remove the solvent present in the applied slurry, thereby forming a ceramic layer 50. Drying can be performed at a temperature suitable for volatilizing the solvent, for example, about 45° C. to 150° C.

[0178] The ceramic particles 55 may be applied under inert and / or dry room conditions, such as dry casting or slurry casting. For example, the method may be performed under low humidity conditions, such as 10% relative humidity (RH) or lower, such as 5% RH, 1% RH (-35°C or lower dew point). The method may be performed at a temperature of 5°C to 150°C.

[0179] Optionally, as Figure 4B and 4D As shown in , after applying the ceramic particles 55 to the first surface 23 of the negative electrode 22, the negative electrode 22 having the ceramic particles 55 present thereon in the ceramic layer 50 can be conveyed through the rollers 78 of the roller press so as to embed at least a portion of the ceramic particles 55 in or on the first surface 23 of the negative electrode 22. A pressure of about 0.1 MPa to about 100 MPa can be applied to the ceramic particles 55 via the rollers 78. When the ceramic particles 55 are applied via slurry casting, a drying or volatilization step can occur before the negative electrode 22 having the ceramic particles 55 disposed thereon is rolled by the roller press. Example

[0180] General information

[0181] Unless otherwise specified below, the ceramic particles used are Li7La3Zr2O 12 Powder (obtained from NEICorporation) (LLZO particles) or α-Al2O3 powder (obtained from Alfa Aesar) (alumina particles). The alumina particles were prepared by grinding with an agate mortar and pestle and a 200 mesh screen. The LLZO particles and the alumina particles had an average particle size of less than 75 μm, for example, in the range of 2 μm to 5 μm.

[0182] Unless otherwise specified below, to form a negative electrode containing ceramic particles, LLZO particles or alumina particles were applied to a lithium metal foil (90 µm thick, on a 10 µm thick stainless steel alloy SUS) via spray casting using a bulb syringe connected to a PTFE tube to deliver the ceramic particles. The electronegative PTFE tube imparts a positive charge to the ceramic particles to improve adhesion to the lithium metal foil. The loading of ceramic particles on the lithium metal foil was varied by changing the number of coating passes. After applying the ceramic particles, a borosilicate glass vial was rolled on the lithium metal foil to embed the ceramic particles into the lithium metal surface.

[0183] Unless otherwise specified below, the batteries prepared in the following examples are each composed of a cathode (LiNi 0.6 Mn 0.2 Co 0.2 O2) (NMC622), the anode prepared as described above, and 30 µl of 1 M LiPF6 in ethyl methyl carbonate and fluoroethylene carbonate as electrolyte with a polyolefin separator (Celgard® C210).

[0184] Unless otherwise specified below, the batteries prepared in the following examples were each tested as follows: Basic cycling protocol: voltage range = 3.0 - 4.3 V; the first 3 cycles were performed at C / 10 charge and discharge rate (0.6 mA); each subsequent cycle was performed at C / 3 charge and discharge rate (2 mA). Fast charge cycling protocol: the same as the basic cycling protocol, except that each 5th cycle starting after the first 3 formation cycles was performed at 2 / 3C rate (4 mA).

[0185] Example 1

[0186] The following anodes were prepared as described above using different LLZO particle loadings as shown in Table 1 below.

[0187] Table 1

[0188] anode LLZO loading 1 <![CDATA[4.5 mg / cm 2 ]]> 2 <![CDATA[4.6 mg / cm 2 ]]> 3 <![CDATA[5.7 mg / cm 2 ]]> 4 <![CDATA[6.1 mg / cm 2 ]]> 5 <![CDATA[6.3 mg / cm 2 ]]> 6 <![CDATA[8.8 mg / cm 2 ]]>

[0189] Figure 5A are photographic images of a control anode (90 µm thick lithium metal foil on 10 µm thick SUS) (510), Anode 2 (515), and Anode 6 (520) without ceramic particles. Figure 5B and 5C is a scanning electron microscope (SEM) image of anode 2 (515). Figure 5C ( Figure 5B A magnified image of the anode (Figure 5A) shows LLZO particles (525) embedded on the surface of a lithium metal anode.

[0190] Example 2

[0191] Cells 1-6 were each prepared using the corresponding anodes 1-6 and the cathodes, separators and electrolytes described above. Control cell A was prepared using the control anode of Example 1 and the cathodes, separators and electrolytes described above.

[0192] Cells 2, 3, 5 and 6 and control cell A were cycled as described above under basic cycling conditions. The results are shown in Fig. 6A and 6B In. Fig. 6A In the graph, the x-axis (610) is the number of cycles, and the discharge capacity / charge capacity (mAh) of control cell A (630) (run in triplicate), cell 2 (640), cell 3 (650), cell 5 (660), and cell 6 (670) are shown on the y-axis (620). Figure 6B , the x-axis (615) is the cycle number, and the coulombic efficiencies of control cell A (630) (run in triplicate), cell 2 (640), cell 3 (650), cell 5 (660), and cell 6 (670) are shown on the y-axis (625).

[0193] Cells 1 and 4 and control cell A were cycled as described above under fast charge conditions. The results are shown in Fig. 7A and 7B In. Fig. 7A In , the x-axis (710) is the number of cycles, while the discharge capacity / charge capacity (mAh) of control cell A (730) (run in triplicate), cell 1 (740), and cell 4 (750) are shown on the y-axis (720). Figure 7B , the x-axis (715) is the cycle number, while the coulombic efficiencies of control cell A (730) (run in triplicate), cell 1 (740), and cell 4 (750) are shown on the y-axis (725).

[0194] Fig. 8A are photographic images of the anodes from control cell A (810), cell 2 (820), cell 3 (830), and cell 6 (840) under base cycling conditions and after formation of an SEI layer thereon. The anode of cell 6 shows LLZO particles (white particles) embedded in the lithium metal SEI. Figure 8B and 8C SEM images of the anode surfaces of control cell A and cell 6, respectively. Figure 8C Also shown are LLZO particles (850) embedded in the lithium metal SEI.

[0195] Example 3

[0196] The following anodes were prepared as described above using different alumina particle loadings as shown in Table 2 below.

[0197] Table 2

[0198] anode Alumina loading 7 <![CDATA[3.25 mg / cm 2 ]]> 8 <![CDATA[5.51 mg / cm 2 ]]> 9 <![CDATA[3.96 mg / cm 2 ]]> 10 <![CDATA[5.25 mg / cm 2 ]]>

[0199] Cells 7-10 were each prepared using the corresponding anode 7-10 and the cathode, separator and electrolyte described above. Control cell A was prepared using the control anode of Example 1 and the cathode, separator and electrolyte described above.

[0200] Cells 7 and 8 and control cell A were cycled as described above under basic cycling conditions. The results are shown in Fig.9A and 9B In. Fig.9A In , the x-axis (910) is the number of cycles, and the discharge capacity / charge capacity (mAh) of control cell A (930) (run in triplicate), cell 7 (940), and cell 8 (950) are shown on the y-axis (920). Fig. 9B , the x-axis (915) is the cycle number, while the coulombic efficiencies of control cell A (930) (run in triplicate), cell 7 (940), and cell 8 (950) are shown on the y-axis (925).

[0201] Cells 9 and 10 and control cell A were cycled as described above under fast charge conditions. The results are shown in Fig. 10A and 10B In. Fig. 10A In the graph, the x-axis (1010) is the number of cycles, while the discharge capacity / charge capacity (mAh) of control cell A (1030) (run in triplicate), cell 9 (1040), and cell 10 (1050) are shown on the y-axis (1020). Fig. 10B , the x-axis (1015) is the cycle number, while the coulombic efficiencies of control cell A (1030) (run in triplicate), cell 9 (1040), and cell 10 (1050) are shown on the y-axis (1025).

[0202] The above description of the embodiments has been provided for the purpose of illustration and description. It is not intended to be exhaustive or to limit the present disclosure. Individual elements or features of a particular embodiment are generally not limited to that specific embodiment, but are interchangeable and can be used in selected embodiments where applicable, even if not explicitly shown or described. It can also be changed in many ways. Such changes should not be regarded as departing from the present disclosure, and all such modifications are intended to be included within the scope of the present disclosure.

Claims

1. Lithium metal electrode, comprising: a first surface; and Ceramic particles comprising: (i) Lithium lanthanum zirconium oxide (LLZO) particles, wherein the LLZO particles are Li7La3Zr2O 12 ;and (ii) aluminum oxide particles; The ceramic particles are present in the following forms: (i) a ceramic layer adjacent to at least a portion of the first surface, wherein the ceramic layer has a thickness of 1 μm to 100 μm; (ii) embedded in said first surface; or (iii) any combination thereof, The LLZO particles were 0.5 g / cm 2 Up to 50g / cm 2 The aluminum oxide particles are present in an amount of 0.4 g / cm 2 Up to 40g / cm 2 The amount exists. 2 . The lithium metal electrode according to claim 1 , wherein the LLZO particles and the aluminum oxide particles each have an average particle size of 100 nm to 20 μm.

3. The lithium metal electrode of claim 1, wherein a binder is present with the ceramic particles and the binder coats at least a portion of the ceramic particles.

4. The lithium metal electrode according to claim 1, wherein the ceramic particles are present in a form embedded in the first surface.

5. The lithium metal electrode of claim 1, wherein the lithium metal electrode comprises metallic lithium.

6. Electrochemical cells, comprising: Lithium metal negative electrode a first surface; and Ceramic particles comprising: (i) Lithium lanthanum zirconium oxide (LLZO) particles, wherein the LLZO particles are Li7La3Zr2O 12 ; (ii) aluminum oxide particles; The ceramic particles are present in the following forms: (i) a ceramic layer adjacent to at least a portion of the first surface, wherein the ceramic layer has a thickness of 1 μm to 100 μm; (ii) embedded in the first surface; or (iii) any combination thereof; a positive electrode comprising a second electroactive material, wherein the positive electrode is spaced apart from the lithium metal negative electrode; a porous separator disposed between the facing surfaces of the lithium metal negative electrode and the positive electrode; and a liquid electrolyte that permeates one or more of the lithium metal negative electrode, the positive electrode, and the porous separator, The LLZO particles were 0.5 g / cm 2 Up to 50g / cm 2 The aluminum oxide particles are present in an amount of 0.4 g / cm 2 Up to 40g / cm 2 The amount exists. 7 . The electrochemical cell of claim 6 , wherein the LLZO particles and the aluminum oxide particles each have an average particle size of 100 nm to 20 μm.

8. The electrochemical cell of claim 6, wherein a binder is present with the ceramic particles and the binder coats at least a portion of the ceramic particles.

9. The electrochemical cell of claim 6, wherein the ceramic particles are present in the form of being embedded in the first surface.

10. The electrochemical cell according to claim 6, wherein the lithium metal electrode comprises metallic lithium, and wherein the second electroactive material is selected from: Li (1+x) Mn2O4, where 0.1 ≤ x ≤ 1; LiMn (2-x) Ni x O4, where 0 ≤ x ≤ 0.5; LiCoO2; Li(Ni x Mn y Co z )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, and x + y + z = 1; LiNi (1-x-y) Co x M y O2, where 0 < x < 0.2, y < 0.2, and M is Al, Mg or Ti; LiFePO4, LiMn 2-x Fe x PO4, where 0 < x < 0.3; LiNiCoAlO2; LiMPO4, where M is at least one of Fe, Ni, Co and Mn; Li(Ni x Mn y Co z Al p )O2, where 0 ≤ x ≤ 1, 0 ≤ y ≤ 1, 0 ≤ z ≤ 1, 0 ≤ P ≤ 1, x + y + z + p = 1 (NCMA); LiNiMnCoO2; Li2Fe x M 1-x PO4, where M is Mn and / or Ni, 0 ≤ x ≤ 1; LiMn2O4; LiFeSiO4; LiNi 0.6 Mn 0.2 Co 0.2 O2 (NMC622), LiMnO2 (LMO), activated carbon, sulfur, and combinations thereof.

11. A method for preparing a lithium metal electrode, the method comprising: applying ceramic particles onto a first surface of a lithium metal electrode to form a ceramic layer comprising ceramic particles, wherein the ceramic layer is adjacent to at least a portion of the first surface and has a thickness of 1 μm to 100 μm; wherein applying the ceramic particles comprises dry casting or slurry casting; and The ceramic particles include: (i) Lithium lanthanum zirconium oxide (LLZO) particles, wherein the LLZO particles are Li7La3Zr2O 12 ; (ii) aluminum oxide particles, The LLZO particles were 0.5 g / cm 2 Up to 50g / cm 2 The aluminum oxide particles are present in an amount of 0.4 g / cm 2 Up to 40g / cm 2 The amount exists. 12 . The method according to claim 11 , wherein the LLZO particles and the aluminum oxide particles each have an average particle size of 100 nm to 20 μm.

13. The method of claim 11, wherein a binder is applied with the ceramic particles and the binder coats at least a portion of the ceramic particles.

14. The method of claim 11, further comprising pressing the ceramic layer to embed the ceramic particles within the first surface.

15. The method of claim 11, wherein applying the ceramic particles is slurry casting, which includes applying a slurry onto the first surface, wherein the slurry comprises a solvent and the ceramic particles. 16 . The method of claim 15 , further comprising drying the slurry applied to the first surface of the lithium metal negative electrode to remove the solvent.

Citation Information

Patent Citations

  • Lithium phosphate coating for lithium lanthanum zirconium oxide solid-state electrolyte powders

    US20210257656A1

  • Protective layers for electrodes and electrochemical cells

    US20170338475A1

  • Lithium secondary battery including electrolyte containing lithium boron compound

    US20190006664A1